Enhancing Speaking and Collaboration Skills Through Project-Based Learning: A Case Study of Indonesian EFL University Students - Gunawan, Iwan Dudy (PROJECT (Professional Journal of English Education), 2025)
This study explores the effectiveness of Project-Based Learning (PBL) in enhancing speaking and collaboration skills among Indonesian university students in an English as a Foreign Language (EFL) context. Employing a qualitative and quantitative case study design, twenty-eight undergraduate students participated in a semester-long PBL program, engaging in a series of communicative and collaborative projects designed to foster active language use. Data were collected through systematic classroom observations, semi-structured interviews, and performance-based assessments. The findings indicate that PBL significantly improved students’ speaking fluency, lexical richness, pronunciation accuracy, and overall communicative competence. Moreover, students demonstrated notable development in teamwork, critical thinking, and problem-solving abilities. Participants also expressed increased motivation, engagement, and autonomy in managing learning tasks. The results suggest that PBL offers substantial pedagogical value in promoting both linguistic proficiency and essential social competencies in EFL learning environments. The study concludes with implications for language pedagogy and recommendations for future research to further explore PBL’s long-term impact.